2022
DOI: 10.3934/mcrf.2021043
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of coprime factor perturbations for robust stabilization of Oseen systems

Abstract: <p style='text-indent:20px;'>Linearization based controllers for incompressible flows have been proven to work in theory and in simulations. To realize such a controller numerically, the infinite dimensional system has to be linearized and discretized. The unavoidable consistency errors add a small but critical uncertainty to the controller model which will likely make it fail, especially when an observer is involved. Standard robust controller designs can compensate small uncertainties if they can be qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In view of stabilization of incompressible Navier-Stokes equations by linear output-feedback controllers, the following considerations are relevant with respect to the estimate (17). It has been shown that an error in the linearization used for controller design, smoothly transfers to a coprime factor perturbation in the transfer function; see [7,30]. Accordingly, with increasing accuracy in the computation of the linearization, the difference becomes arbitrarily small such that, eventually, a robust controller based on a numerically computed linearization will be able to stabilize the system.…”
Section: The Normalized H ∞ Problem and Low-rank Robust Controllersmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of stabilization of incompressible Navier-Stokes equations by linear output-feedback controllers, the following considerations are relevant with respect to the estimate (17). It has been shown that an error in the linearization used for controller design, smoothly transfers to a coprime factor perturbation in the transfer function; see [7,30]. Accordingly, with increasing accuracy in the computation of the linearization, the difference becomes arbitrarily small such that, eventually, a robust controller based on a numerically computed linearization will be able to stabilize the system.…”
Section: The Normalized H ∞ Problem and Low-rank Robust Controllersmentioning
confidence: 99%
“…This rules out the standard linear quadratic Gaussian (LQG) design that has no guaranteed stability margin [21]. A general remedy is provided by H ∞ -controllers that, provably, can compensate for linearization errors [7,14,30], discretization errors [8,19], and truncation errors [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation